The Evaluation of Flow-Mediated Vasodilation in the Brachial Artery Correlates With Endothelial Dysfunction Evaluated by Nitric Oxide Synthase Metabolites in Marfan Syndrome Patients - Lomelí, Oscar; Pérez-Torres, Israel; Márquez, Ricardo; Críales, Sergio; Mejía, Ana M.; Chiney, Claudia; Hernández-Lemus, Enrique; Soto, Maria E. (Frontiers in Physiology, 2018)
Marfan syndrome (MS) is of the most common connective tissue disorders. Although most patients have mutations in the fibrillin-1 gene (FBN1) and more than 1,700 mutations have been described, there are no mutations in less than 10% of patients. Aortic dilation is the most important complication; it involves chronic inflammatory processes and endothelial dysfunction. Prospective study from March 2015 to January 2017, in a cohort of 32 patients of MS confirmed by Ghent criteria and 35 controls of both genders, with a median age of 26 years (18–56). Patients had no comorbidities such as diabetes, hypertension, and/or neoplasms. They were not being treated with statin, NSAIDs, calcium antagonists, oral nitrates, and/or beta-blockers during 7 days prior to the study and patients with smoking history in the last 4 years. Controls were matched by age and gender. We analyzed endothelial dysfunction by flow-mediated vasodilation in the brachial artery, determining the maximum peak flow in the reactive hyperemia phase with a Philips Envisor device with Doppler capability. Its correlation with serum levels of biological markers that could participate in endothelial dysfunction pathways such as NO3−/NO2− ratio, NO2−, citrulline, TNFα, IL-1, IL-6, IL-10, IL-8, osteopontin, ICAM, VCAM, and NO3−/NO2− was determined. Endothelial dysfunction was found in 21 MS patients (65%). The aortic annulus (AAo) was of 27 mm (22–40) and 24 mm (22–30) (p = 0.04) in MS patients with and without dysfunction. The level of NO3−/NO2− ratio, was of 108.95 ± 12.05 nM/ml in controls vs. 170.04 ± 18.76 nM/ml in MS (p = 0.002), NO2− was of 33.78 ± 3.41 vs. 43.95 ± 2.59 nM/ml (p = 0.03), citrulline 62.65 ± 3.46 vs. 72.81 ± 4.35 μMol/ml (p = 0.06). VCAM median was 39 pg/ml (0–86) vs. 32 pg/ml (11–66) (p = 0.03), respectively. The correlation of VCAM with triglycerides (TG) was of 0.62 (p = 0.005). There were no differences in TNFα, IL-1, IL-6, IL-8, IL-10, and osteopontin. MS endothelial dysfunction is related to aortic diameters, and increased levels of VCAM, L-citrulline and NO3−/NO2− ratio, NO2−. VCAM-1 has a significant correlation with TG and could play a significant role in endothelial dysfunction.